Ice Jams, Winter 2001-2002 - ENGINEER RESEARCH AND DEVELOPMENT CENTER HANOVER NH COLD REGIONS RESEARCH AND ENGINEERING LAB (2003)
During winter months, ice may form on rivers, lakes, and streams in cold regions. Ice jams forms during initial ice cover formation as the ice accumulates, restricting water flow (freezeup jam), and also when the ice cover breaks apart and begins to move (breakup jam). When rivers become jammed with ice, riverine communities upstream from an ice jam can suffer severe effects as a result of backwater flooding and structural impacts of ice. Excessive water and ice associated with ice jams often causes damage to bridges, roads, and buildings. Roads and runways can be forced to close, and bridges can be damaged or destroyed, delaying or limiting emergency aid in evacuation situations. Transportation of beating fuel and other necessary cargo can be temporarily halted as both roadways and waterways are affected. Areas downstream from jams can also be affected if they experience sudden decreases in flow as backwater occurs upstream. These decreases in flow can cause water intakes to become exposed, threatening water supplies to municipalities, industries, and power plants. Communities downstream of the jam can also be affected by the rapid surge of water and ice that occurs when a jam releases. The original document contains color images.